Analysis Of Consumer Satisfaction Level with Bulog Rice In The Mobile Market Activities Program In Medan City: English - Syahfitri, Alfi; Musika Lubis, Mitra (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
Bulog (Logistics Agency) is one of the state-owned public companies engaged in food logistics. The general task of Bulog is to carry out development in the field of logistics management through the management of inventory, distribution, and price control of rice, as well as logistics service efforts in accordance with applicable laws and regulations. This research aims to analyze the factors that influence consumer satisfaction levels and to analyze how consumer satisfaction levels with Bulog rice in the mobile market program in the city of Medan. This research was conducted in the Medan Area and Medan Denai sub-districts. The research method used in this study is of the quantitative type, with the sample determination using the Convenience Sampling technique. In this study, the sample size used is 50 respondents. The data analysis used in this study includes multiple linear regression and the Customer Satisfaction Index (CSI). The results of this study indicate that the Price variable (X1) and the Product variable (X2) significantly affect customer satisfaction with Bulog rice in the mobile market program in Medan City, while the Promotion variable (X3) and the Place variable (X4) do not significantly affect customer satisfaction with Bulog rice in the mobile market program in Medan City. Based on the calculation of the Customer Satisfaction Index (CSI), the satisfaction level obtained is already within the "very satisfied" criteria, which is 86.4%.